Source and Impact of the EGF Family of Ligands on Intestinal Stem Cells - Abud, Helen E.; Chan, Wing Hei; Jardé, Thierry (Frontiers in Cell and Developmental Biology, 2021)
Epidermal Growth Factor (EGF) has long been known for its role in promoting proliferation of intestinal epithelial cells. EGF is produced in Paneth niche cells at the base of crypts in vivo and is routinely added to the medium to support the growth of intestinal organoid cultures ex vivo. The recent identification of diverse stromal cell populations that reside underneath intestinal crypts has enabled key growth factor cues supplied by these cells to be characterized. The nature of these signals and how they are delivered to drive intestinal development, daily epithelial homeostasis and regeneration of tissue following injury are being investigated. It is clear that aside from EGF, other ligands of the family, including Neuregulin 1 (NRG1), have distinct roles in supporting the function of intestinal stem cells through the ErbB pathway.